Replicator dynamics in value chains: explaining some puzzles of market selection. (2nd January 2019) - Cantner, Uwe; Savin, Ivan; Vannuccini, Simone
Abstract: The pure model of replicator dynamics provides important insights in the evolution of markets but has not met with much empirical support. This article extends the model to the case of firms vertically integrated into value chains (VCs). Through an extended analytical model and numerical simulations, we show that (i) by taking VCs into account, the replicator dynamics may reverse its effect. In these "regressive developments" of market selection, firms with low fitness expand because of being integrated with highly fit partners, and the other way around; (ii) allowing a partner's switching re-introduces selection forces into the upper layers of VCs; and (iii) periods of instability in the early stage of the industry life cycle may be the result of an optimization' of partners within a value chain, thus providing a novel and simple explanation of the evidence discussed earlier in the literature.